The Productivity and Future Growth Potential of Indonesia - Ikhsan, Mohamad; Indrawati, Sri Mulyani; Virananda, I Gede Sthitaprajna; Abdi, Zihaul (UI Scholars Hub, 2022)
The output per worker of Indonesia has been on a downtrend since 2010, with total factor productivity (TFP) and capital stock largely stagnant if not declining. This paper discusses stylized facts that may explain recent trends in the productivity and growth potential of Indonesia. The decomposition of output per worker reveals the declining contribution of human capital, which is also most negative among peer countries. The growth in labor productivity has been concentrated within sectors, implying room for gains from labor reallocations. A substantial share of employment and credit in Indonesia has shifted to the relatively unproductive service sectors, particularly wholesale and retail trade. In terms of firm dynamics, the contribution of large firms in Indonesia has been lackluster compared to regional peers while the productivity of micro, small and medium enterprises remains stagnant. Considering that human capital and TFP measures of Indonesia are lagging behind middle-income peers, there is wide scope for Indonesia to catch up. However, the potential output of Indonesia also faces new risks from the COVID-19 pandemic. We expect that theÂ short-term effect of the pandemic on capital accumulation and the long-term effect on human capital pose the highest risk while labor inputs appear to be more resilient. Meanwhile, the potential productivity gains from accelerated digital adoption and sectoral reallocations are more uncertain.